Water Gymnastics as a Therapeutic Method to Improve Motor Planning in Children with Intellectual Disability - Diyana Georgieva; Veselina Ivanova (OVS LLC, 2023)
Study purpose. This paper is devoted to an experimental study aimed to identify the effects of water gymnastics as a therapeutic method for improving motor planning in children with intellectual disability studying in general and special education institutions. Materials and methods. Twenty-three children (13 boys and 10 girls) aged from 6 to 11 years (x̅ = 8.61) participated in the study.  Three neuropsychological tests were used to study motor function: Sequential alternation of fist-palm-side, Graphic test "Fence", and Fist-palm. Data were collected before and after participation in an 11-month therapy course conducted in a water environment. Descriptive analysis and One-way analysis of variance (ANOVA) were applied to process the empirical material. Cohen's η was used to interpret the effect size attributed to the therapeutic intervention. Results. Programming, regulation, and control, as the main components of motor planning, showed improvement after the children participated in the organized sessions, as evidenced by the large or larger than typical effect size η=[0.37:0.45+] recorded and the nonsignificant differences between groups differentiated by level of intellectual disability, age, and gender at the control measurement stage (p > 0.05). Conclusions. The results lead to the generalization that at the final stage of the study, all three factors (level of intellectual disability, age and gender) had no significant influence on the development of motor planning, confirming the effects of water gymnastics as a technology for its improvement.